Students with Intensive Needs in an Inclusive Education System: A Literature Review - Naeemy, Mohammad Idrees; Yoneda, Hiroki (Department of Special Education, 2024)
Educating students with various types and degrees of disabilities in regular classrooms remains challenging. Despite the global agenda and push for inclusive education, students with disabilities, particularly those with multiple and severe disabilities, are still being educated in segregated environments. In this qualitative study of peer-reviewed research literature, we aim to understand students with intensive needs (SINs), their current situation in inclusive education systems in developed and developing countries, and the best approaches to how they are being or should be educated in inclusive education systems. The results indicate that students who experience severe challenges in their physical, intellectual, developmental, mental, or emotional capabilities, or a combination of these factors, could be called SINs, as they have a set of significant academic, communication, or behavioral challenges across various domains. Currently, most SINs worldwide spend 20% or more of their educational time outside of the regular school day class. We suggest that utilizing Universal Design for Learning (UDL) principles as part of the opportunities to learn (OTL) framework and the concept of Communities of Practice (CoP) would be useful in designing an inclusive education model in which SINs will not only be included but also benefit from the curriculum in a regular classroom. Future research should focus on the implementation of suggested inclusive education models for SINs.